Análise estatística do desempenho em fadiga de arames soldados da armadura de tração de umbilicais submarinos - Nascimento, Brenno Lima (2023)
The world's growing need for energy has motivated the search for oil and gas reserves in ever deeper water depths. The exploiting these resources in such challenging environments requires that the subsea umbilical's tensile armor be able to maintain the structural integrity of the umbilical for the lifetime it was designed as, ensuring remote operational control of the subsea production systems. For this to be satisfied, it is essential to perform fatigue tests on the welded joints of wires that compose the umbilical armor, obtained by upset welding process, as they are usually more critical than the base metal. For convenience, the results of these tests are analyzed by a standard methodology established by standards that do not always approximate the real distribution of the data for all conditions and to compensate for this, designers end up overestimating the predictions of the S-N curves. This study aimed to evaluate the metallurgical and mechanical aspects of this type of weld and the predictions of the S-N curves obtained by the standards methodology and the alternative Weibull distributions. This evaluation involved chemical and microstructural characterization, microhardness, tensile and fatigue uniaxial tests of the wire weld. The Weibull S-N curves showed greater robustness and the conservatism of the S-N curves obtained by standards was confirmed.